Effectiveness of Spirulina platensis as a bioremediator candidate for vaname shrimp (Litopenaeus vannamei) wastewater - Hartami, Prama; Mauliyani, Mauliyani; Erniati, Erniati; Masyithah, Putri; Kurniawan, Rizky; Suhaila, Nurul; Muliani, Muliani; Rusydi, Rachmawati (Universitas Malikussaleh, 2022)
The purpose of this study was to determine the effectiveness of Spirulina platensis for remediation of vannamei shrimp culture waste. The method used in this study was a Non-Factoral Completely Randomized Design (CRD) with 4 treatments and 3 replications, namely (A) Control; (B) 50% waste (1500 ml waste + 1500 ml water) + technical fertilizer + Spirulina inoculant; (C) 75% waste (2,250 ml of waste + 750 ml of water) technical fertilizer + Spirulina inoculant; (D) 100% waste + technical fertilizer + Spirulina inoculant. Data analysis used ANOVA with 95% confidence level. The results showed that the use of Spirulina platensis as a remediation agent for vaname shrimp culture had a significant effect on reducing levels of waste ammonia, phosphate, nitrate, and density of Spirulina platensis (Fcount > Ftable 0.05).Keywords: Bioremediator; Innoculant; Vanname shrimp; Waste water